2002
DOI: 10.1603/0022-2585-39.2.324
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Dipstick Malaria Sporozoite Panel Assay for Detection of Naturally Infected Mosquitoes

Abstract: The determination of the presence or absence of malaria sporozoites in wild-caught Anopheles mosquitoes remains an integral component to the understanding of the transmission dynamics in endemic areas. To improve that capability, there has been on-going development of a new device using dipstick immunochromatographic technology for simplifying the testing procedure and reducing the time required to obtain results. As part of a larger multi-center effort, we evaluated the sensitivity and specificity of a protot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 17 publications
2
12
0
Order By: Relevance
“…The V-MAP assay was sensitive and speciÞc for each of the parasites evaluated, simple to use, rapid (results obtained in 15 min), and could be used in the Þeld. Studies by Bangs et al (2002) in Indonesia and at a variety of other laboratories throughout the world (Ryan et al 2001 also document the excellent performance of this assay.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The V-MAP assay was sensitive and speciÞc for each of the parasites evaluated, simple to use, rapid (results obtained in 15 min), and could be used in the Þeld. Studies by Bangs et al (2002) in Indonesia and at a variety of other laboratories throughout the world (Ryan et al 2001 also document the excellent performance of this assay.…”
Section: Discussionmentioning
confidence: 80%
“…The V-MAP assay determines the presence or absence of speciÞc peptide epitopes of CS protein of P. falciparum and two P. vivax strains (variants 210 and 247). Bangs et al (2002) reported that the performance of the V-MAP assay was comparable to that of the CS ELISA in Indonesia and Papua New Guinea. More recently, Ryan et al (2002) analyzed data from over 40,000 assays conducted at 16 different test centers from around the world and found that performance of the V-MAP was comparable to the CS ELISA.…”
mentioning
confidence: 97%
“…The studies performed to evaluate the malaria sporozoite antigen panel assay (MRP dipstick assay or VecTest™) for detecting naturally infected mosquitoes show that it is an optimal diagnostic method for use in malaria endemic areas [13,14]. These surveys compared MRP dipstick assay with another serological diagnostic probe (ELISA assay) for detecting CSP antigen.…”
Section: Discussionmentioning
confidence: 99%
“…A test was interpreted as positive when at least two lines appeared on the strip and as negative if only the control line was present. Strips were also examined one month after testing to note retention of bands [14]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation